Transition metal self-assembly of dithiocarbamate based anion receptors - Berry, N; Pratt, MD; Fox, O; Beer, P (2001)
Novel macrocyclic and acyclic transition metal dithiocarbamate based anion receptors, prepared via metal mediated self-assembly, strongly bind anions, and in the case of L2 electrochemically recognise carboxylate, chloride and dihydrogen phosphate.